2018
DOI: 10.1002/asia.201801080
|View full text |Cite
|
Sign up to set email alerts
|

Optimizing the Thermoelectric Performance of Poly(3‐hexylthiophene) through Molecular‐Weight Engineering

Abstract: Poly(3-hexylthiophene) (P3HT) films with various molecular weights (MWs) were successfully prepared, and both their molecular structures and thermoelectric (TE) properties were investigated. It was found that the molecular weight of P3HT had an important effect on the carrier-transport properties by affecting the molecular structure and, as a result, also had an effect on the TE performance. The electrical conductivity of the P3HT films first increased upon increasing the molecular weight and then decreased at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
23
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(24 citation statements)
references
References 29 publications
1
23
0
Order By: Relevance
“…However, the surface topography at higher MWs seems to become slightly smoother, which could be attributed to the increase of polymer chain lengths. It is also consistent with previously published reports describing the effect of MW on the electrical properties of P3HT films [42][43][44]. Variations in the topography among samples could be attributed to the difference in the evaporation rate of the solvent and the solidification of the polymer in different solutions.…”
Section: Methodssupporting
confidence: 93%
See 1 more Smart Citation
“…However, the surface topography at higher MWs seems to become slightly smoother, which could be attributed to the increase of polymer chain lengths. It is also consistent with previously published reports describing the effect of MW on the electrical properties of P3HT films [42][43][44]. Variations in the topography among samples could be attributed to the difference in the evaporation rate of the solvent and the solidification of the polymer in different solutions.…”
Section: Methodssupporting
confidence: 93%
“…As mentioned before, the electrical properties of P3HT films with various MWs have been investigated in the literature. However, to the best of our knowledge, there is only one report which compares the thermoelectric properties of P3HT thick films with three different MWs [42]. Regardless of that report, the correlation between chain lengths, morphology, and thermoelectric parameters has not yet been completely studied.…”
mentioning
confidence: 99%
“…Compared to inorganic thermoelectric materials, these organic thermoelectric materials exhibit some unique advantages, such as a low thermal conductivity, highly adjustable molecular structures, the potential for low cost, and facile processing into versatile forms . Until recently, several conducting polymers, including polythiophene, polypyrrole, polyaniline, polyfluorene, and their derivatives, have been widely studied as thermoelectric materials, and some conjugated polymers with new structures have also been explored . For instance, Yang et al designed and synthesized two donor–acceptor (D–A)‐type conjugated polymers and effectively enhanced the thermoelectric properties of D–A conjugated polymers through donor engineering; Liu et al tailored the density of states of D–A conjugated polymers, and as a result, improved the power factor dramatically .…”
Section: Methodsmentioning
confidence: 99%
“…[8][9][10][11][12] due to their low toxicity, low thermal conductivity and mechanical flexibility. Recent results have shown that CPs are among the most promising materials for application in flexible thermoelectric generators [13][14][15][16][17]. For example, poly(3,4-ethylenedioxy-thiophene) (PEDOT) with a high thermoelectric figure of merit (ZT) of 0.45 has been reported [18], which stimulated the investigation of CPs to be used for thermoelectric generators.…”
Section: Introductionmentioning
confidence: 99%
“…Organic materials generally possess large Seebeck coefficients (S) and low thermal conductivity [13][14][15][16][17][18][19], therefore, the main challenge of achieving high-performance OTEs is how to improve the electrical conductivity of CPs without sacrificing their large Seebeck coefficients and low thermal conductivity [20,21]. Many strategies have been attempted to improve the conductivities of CPs (such as structural manipulations [22], strengthening the ordering of polymer packing [23], efficient doping [24], and forming composites with highly conductive inorganic materials [25], etc.…”
Section: Introductionmentioning
confidence: 99%